Palladium-Catalyzed Oxidative Allylic Alkylation of N-Hydroxyimides - Ayyagari, Narasimham; Sunnam, Sunil Kumar; Ahire, Milind M.; Yang, Minxi; Ngo, Kevin; Belani, Jitendra D. (Synlett, 2020)
A palladium-catalyzed oxidative C–H allylic alkylation of N-hydroxyimides has been developed. This transformation provided valuable N-allyloxypyrrolidinediones in moderate to excellent yields using operationally simple, ligand free, and mild reaction conditions. The reaction tolerated broad and variable substituents on allylarenes and N-hydroxyimides.
Keywords: allylic C–H activation; palladium; N-hydroxyimides; C–O bond formation